Tourism and the mining boom: Golden age, or golden shower? - Hughes, Michael (Council for Australasian Tourism and Hospitality Education, 2012)
The Western Australian (WA) mining boom is touted by government for the significant revenue and regional socio- economic benefits it allegedly generates. With State Government support, the resources sector is now expanding into new remote regions, including iconic WA tourism destinations. This is causing conflict based on contested views and land uses. Proponents argue that their industry creates wealth and employment opportunities for the regions they operate in. Those opposed to such activity argue that the benefits are exaggerated and costs are significantly high. This paper presents the case of an onshore LNG plant proposal for the West Kimberley coastal region, near Broome. A WA State Government commissioned assessment concluded the development will have a minimal impact on tourism and will benefit the local community. A review of published evidence suggests there will be considerable costs to communities and tourism. These issues are discussed in the context of tourism development and its contribution to the region.